Penerapan Etika Kristen dalam Pendidikan Anti Korupsi di Keluarga - Sapto Sunariyanti (Sekolah Tinggi Theologia Nazarene Indonesia, 2018)
Nowadays, coruption is present on Indonesia government bureaucracy, also exist in society. Corruption need to prevent as early as possible and start from smallest thing called family. This journal aim to explain about how to apllied Christian’s ethics to anti-corruption education on family. This topic analyze by biblical scripture approach and chistian’s ethics. Bible tell implicitly that corruption is disobidience to the God by the story of Annanias and Safira also the story of Judas Iskaroit. Futhermore, corruption have the meaning of sin that must be accounted to the God personally. Conclusion, Christian’s ethics that should be applied on anti-corruption education of family are involved honestly and integrity morals, the fear of the Lord understanding, and gratef1ul feelings.